Clinical Holistic Medicine: Chronic Pain in the Locomotor System - Søren Ventegodt; Joav Merrick (The Scientific World Journal)
Most pains from the locomotor system arise due to involuntary, chronic tensions in the muscles or other tissues. When the patient is motivated, the pain is easily cured in most of the cases by using the tools of consciousness-based medicine, primarily therapeutic touch, conversation, and coaching the patient in a positive philosophy of life. The pains are often caused by “blockages” that may cause problems other than just pain. Often it turns out that the blocked areas develop actual physical damage over time: a slipped disk in the back, articular degeneration, or osteoarthritis when the cartilage is affected, can often be explained in this way. Apparently, the exact areas where the blockage is situated cause cellular problems, disrupting cellular order. The holistic process theory of healing and the related quality of life theories state that return to the natural state of being is possible, whenever the person gets the resources needed for existential healing. The resources needed are “holding” in the dimensions of awareness, respect, care, acknowledgment, and acceptance with support and processing in the dimensions of feeling, understanding, and letting go of negative attitudes and beliefs. The preconditions for holistic healing are trust and the intention for the healing to take place. Case stories of holistic treatment of patients with chronic back pain, low back pain, muscle problems, knee pain, and symptoms of rheumatoid arthritis are discussed with exercises relevant for patients with these conditions in the holistic clinic.